PP.27.21: CORRELATION BETWEEN SERUM URIC ACID AND LEFT VENTRICULAR MASS IN ESSENTIAL HYPERTENSION. (June 2015) - Rinaldi, E.; Cosentino, E.; Bentivenga, C.; Iamino, I. Ricci; Rosticci, M.; Cicero, A.F.G.; Esposti, D. Degli; Borghi, C.
Abstract : Objective: Several epidemiological studies have addressed the concept that serum uric acid (SUA) level correlates with blood pressure levels and can predict the future development of hypertension. However, it is still controversial whether its role goes beyond hypertension development and extends to subsequent target organ damage, such as left ventricular hypertrophy (LVH). SUA may induce LVH through an inflammatory effect which promote cardiac hypertrophy and through an activation of the renin-angiotensin-aldosterone system which generate hypertrophy and hyperplasia of myocytes and fibrosis of the heart. Aim of the study was to investigate the relationship between serum UA levels with left ventricular mass in hypertensive patients. Design and method: 51 patients with essential hypertension (mean age 70 ± 11 years; range 49–87, F 37.7 %; M 62.3 %). Each patient underwent a standardized medical history and examination, laboratory tests and echocardiographic assessment with the determination of left ventricular mass index (LVMI). Results: A positive significant correlation between SUA and LVMI (P = 0.029) was observed, suggesting that increased urate levels are associated with a higher myocardial mass. After adjusting for mean arterial pressure and age in standard multiple linear regression analysis, UA levels remains independently associated with LVMI. Figure. No caption available. Conclusions: These results demonstrate that UA is independently associated with LVMI and they suggest that LVH may be attributable to an increase in UA itself, via stimulation of endothelial dysfunction, smooth muscle cell proliferation, and inflammation. The association between UA and CVD events may be introduced in part because of a direct association of UA with LVM. In hypertensive subjects, assessment of UA levels may help to refine CVD risk stratification.